Characteristics of the therapeutic communities and regulations for the correct behaviour of the personnel - Bompiani, Adriano (Medicina e Morale, 1994)
The increasing importance of the therapeutic communities (TC) in the fight against drug addiction in various countries over the last few years has led the author, in this article, to consider the various types of TCs in order to identify the correct behaviour that should exist there. In fact, in Italy, even though the TCs have bcen recognized as having a role as auxiliary organizations of the public structures that assist drug addicts, there are stili no regulations on the types of TC, internal organization, characteristics of the management and checks on how they are run. After briefly outlining the history of the TCs and illustrating their characteristics, including the description of the development of the public services for drug addicts (SERT), there is the question of the size and the operative criteria of the psychoergotherapeutic activity carried out at the TCs. The author analyses the motivations and the idea of the community in the personnel as thought of by their "founders". In this way common paths are identified in the various methods used in the TCs: the "education for life''; the personalization of the rehabilitation programme; the refusal of any imposition and violence; the sharing of responsibilities, also through work as a formative instrument of the personality. However, the question of the evaluation of the results obtained in the TCs is stili open. The article concludes with the guidelines approved in Aprii 1993 by the TC and SERT staff in the National Committee for the coordination of antidrug action in Italy. Although this document is not binding, it represents an effort towards an awareness of the problems and a moral commitment of the personnel regarding valid principles in the fight against drug addiction.